Intestinal Microbes-based Analysis of Immune Mechanism of Childhood Asthma: Intestinal Microbes-based analysis - Mo, Miaojun; Wang, Junrong; Gu, Hongdan; Zhou, Junfen; Zheng, Changhua; Zheng, Qi; Chen, Hairui (Cellular and Molecular Biology, 2022)
This work was developed to explore the relationship between intestinal microflora composition and immune function changes in children with asthma and to provide theoretical references for clinical diagnosis and treatment. Forty-eight children with asthma who received standardized treatment in the outpatient department of pediatric respiratory asthma in Children's Hospital were selected as the research objects, which were rolled into 24 cases of S0 group (complete control) and 24 cases of S1 group (incomplete control group). In addition, ten healthy children with general data matching the research objects were selected as a blank control (D0 group). The intestinal microbial composition and immune function indexes of each group were detected. The results showed that there were differences in the intestinal microbes of the three groups of children with Bifidobacterium, Megasphaera, Oscillibacter, Bilophila, and f_Ruminococcaceae. Among them, the proportions of Bifidobacterium, Megasphaera, and f_Ruminococcaceae in the intestinal microbes of the children in the S1 group were notably less than those in the S0 and D0 groups. The proportion of these three bacterial genera in the S0 group was also considerably smaller than that in the D0 group (P<0.05). In addition, the CD3+ levels of children in the S1 group were notably lower than those in the S0 and D0 groups, while the CD4+ and CD4+/CD3+ were higher than the S0 and D0 groups (P<0.05). The differences between CD3+, CD4+, and CD4+/CD3+ in the S0 and D0 groups were not considerable (P<0.05). The proportions of Bifidobacterium, Megasphaera, f_Ruminococcaceae, and Parasutterella in children with intestinal microbes were significantly positively correlated with CD3+ levels (P<0.05), and significantly negatively correlated with CD4+ and CD4+/CD3+ levels (P<0.05). In short, children with different levels of asthma control had a certain degree of flora disorder and decreased immune function in the intestinal flora. The decrease in the relative abundance of Bifidobacterium, f_Ruminococcaceae of Firmicutes, and Parasutterella of Riken Bacteria, and the increase in the relative abundance of Oscillatoria meant the decline of the immune function of the children.